Comprehensive Guide to Randomized Controlled Trials in Radiology: Everything You Need to Know - Shreya Shukla; Abhishek Mahajan (Indian Journal of Radiology and Imaging)
Evidence-based medicine integrates clinical research, personal expertise, and patient values. The most robust forms of clinical evidence, such as randomized controlled trials (RCTs) and prospective studies, provide the strongest support for medical decision-making. RCTs are vital in radiology for evaluating new imaging technologies, contrast agents, and therapeutic procedures, despite challenges in translating preclinical findings to clinical practice. This guide discusses the history, principles, methodologies, and applications of RCTs in radiology, highlighting their role in advancing the field and supporting evidence-based practice.